Case-studies, problem based learning and simulations in biomedical teaching: a literature review - Jesus, Ângelo (2017)
This paper aims to review the use and application of CBL, PBL and SBT in biomedical education, as well as to review significant differences found in studies trying to assess the effectiveness of these pedagogical approaches in promoting learning and higher order thinking. Our research method was a systematic search and review of published journal articles and conference proceedings, between 1990 and 2011 in several databases. The study shows that the main area where we can find CBL, PBL or SBT is the Medical field, followed by Pharmacy, and Nursing and Allied Health in similar proportions. Generally, studies agree when referring the advantages of CBL, PBL and SBT regarding traditional teaching. There is however a lack of evidence when comparing learning effectiveness among the three approaches. The main conclusions show that although the situations presented are, in general, success cases, one must constrain in making generalized affirmations regarding significant difference in student learning and development, because no long term controlled studies have been conducted. Students’ perspectives and attitudes towards these learning approaches are, in general, positive. However it seems important to develop more consistent research in this field, namely, longitudinal studies with larger samples